2022
DOI: 10.3389/fcvm.2022.916770
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the predictive value of electrocardiographic indicators in the diagnosis and prognosis of children with vasovagal syncope

Abstract: Neurally mediated syncope (NMS) is a common type of syncope in children in clinical practice, among which vasovagal syncope (VVS) is the most frequent. In recent years, more and more studies have been carried out to assess the diagnosis and prognosis of VVS. The electrocardiographic indicators such as heart rate variability (HRV), QT dispersion (QTd), P-wave dispersion (Pd), ventricular late potentials (VLP), deceleration ability of heart rate (DC), etc., are easy to obtain and inexpensive. With the help of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In addition to seriously affecting the physical and mental health and quality of life of the children, the parents are also under great psychological pressure. Therefore, paying attention to the psychological feelings and service requirements of children with VVS and their parents, especially the health education of children and their parents, and improving their compliance, are the key links to promoting the rehabilitation of children ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to seriously affecting the physical and mental health and quality of life of the children, the parents are also under great psychological pressure. Therefore, paying attention to the psychological feelings and service requirements of children with VVS and their parents, especially the health education of children and their parents, and improving their compliance, are the key links to promoting the rehabilitation of children ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SDANN, one time-domain indicator of HRV, reflects sympathetic nerve activity ( 27 ). Previous studies reported the diagnostic value of HRV for VVS ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, others revealed that venous blood routine hemoglobin concentration and mean corpuscular hemoglobin were candidate biomarkers in predisposition to syncope recurrence (7). Further, heart rate variability (HRV), body mass index (BMI), and therapeutic regimens can also affect the prognosis of VVS (8)(9)(10). Thus far, no consensus has been attained which and how many factors actually precipitate the development of recurrent syncope in children with VVS, likely due to differences in genetic underpinnings, statistical power or participant characteristics.…”
Section: Introductionmentioning
confidence: 99%